2020
DOI: 10.25271/sjuoz.2020.8.4.773
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of N-GaAs Substrate Orientations on The Electrical Performance of PANI/N-GaAs Hybrid Solar Cell Devices

Abstract: This paper reports the fabrication and electrical characterization of hybrid organic-inorganic solar cell based on the deposition of polyaniline (PANI) on n-type GaAs substrate with three different crystal orientations namely Au/PANI/(100) n-GaAs/(Ni-Au), Au/PANI/(110) n-GaAs/(Ni-Au), and Au/PANI/(311)B n-GaAs/(Ni-Au) using spin coating technique. The effect of crystallographic orientation of n-GaAs on solar cell efficiency of the hybrid solar cell devices has been studied utilizing current density-voltage (J-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[ 113 ] It was observed that the solar cell efficiency is higher in PANI (200 nm)/(311) A n‐GaAs device than those with (100) or (311) B n‐GaAs substrates. However, the efficiency for PANI with a lower thickness (52 nm) deposited on (311) B n‐GaAs plane, which was investigated by Mustafa et al, [ 114 ] is better than that of PANI (200 nm) fabricated on (311) n‐GaAs devices, as reported by Jameel. Therefore, it is clear that the thickness of PANI and orientation of n‐type GaAs substrate play an important role in enhancing the solar cell efficiency of the organic/inorganic devices.…”
Section: Device Structure and Performancementioning
confidence: 94%
See 1 more Smart Citation
“…[ 113 ] It was observed that the solar cell efficiency is higher in PANI (200 nm)/(311) A n‐GaAs device than those with (100) or (311) B n‐GaAs substrates. However, the efficiency for PANI with a lower thickness (52 nm) deposited on (311) B n‐GaAs plane, which was investigated by Mustafa et al, [ 114 ] is better than that of PANI (200 nm) fabricated on (311) n‐GaAs devices, as reported by Jameel. Therefore, it is clear that the thickness of PANI and orientation of n‐type GaAs substrate play an important role in enhancing the solar cell efficiency of the organic/inorganic devices.…”
Section: Device Structure and Performancementioning
confidence: 94%
“…On the other hand, PANI is potentially useful to construct heterojunctions with inorganic semiconductors such as silicon (Si) and gallium arsenide (GaAs) substrates for electronics and photovoltaic applications. [115][116][117] However, reported PCEs of these types of hybrid devices are still very low (less than 1% [113,114,117,118] ) due to the moderate conductivity of PANI. The sole relative report with a higher PCE (2.75% [40] ) utilized composite materials by adding graphene nanoparticles (GNP) in PANI.…”
Section: Device Structuresmentioning
confidence: 99%
“…In addition, Jameel et al [12] utilized spin coating to deposit organic polymer PANI on GaAs substrates with different orientations. Moreover, the effect of the rotation number of spin coating on the thickness of hybrid solar cell devices was studied by Mustafa et al [13]. The authors obtained that the thicknesses of the deposited PANI layer over GaAs are 58 ± 2 nm, 58 ± 2 nm, and 54 ± 2 nm for sample spinning at 2000, 3000, and 4000 rpm, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of the rotation number of spin coating on the thickness of hybrid solar cell devices was studied by Mustafa et al [13]. The authors obtained that the thicknesses of the deposited PANI layer over GaAs are 58 ± 2 nm, 58 ± 2 nm, and 54 ± 2 nm for sample spinning at 2000, 3000, and 4000 rpm, respectively [13]. Furthermore, it has been determined that the number of rotations has a considerable effect on the thickness of the coating layer and the efficiency of PANI/TiO2/FTO-Glass Photoanode has been studied [14].…”
Section: Introductionmentioning
confidence: 99%